Deposição atmosférica e composição química da água de chuva. - Valdenor Nilo de Carvalho Junior (Revista Tecnologia, 2009)
The impact of chemical composition of rain on groundwater and surface water final solute concentration is an important aspect of geochemical studies. Considering the pluviometric precipitation as uniform from quality point of view it may lead to erroneous conclusions about its hydrochemical behavior in the environment. This work presents critical concepts rainon the sources of rainwater chemical composition. It describes main hydrochemical process in the atmosphere, discussing basic aspects about the formation of ionic components for pluviometric precipitation.